Demographic Dynamics of Nepal: Key Findings from the National Population and Housing Census 2021 - Prachhai , Deepak Bahadur (Patan Prospective Journal, 2025)
The National Population and Housing Census 2021, conducted by the National Statistics Office (NSO), represents the twelfth nationwide census of Nepal since 1911. Originally scheduled for June 2021 but postponed due to the COVID-19 pandemic, the census was carried out in November 2021, with results officially released in March 2023. This article provides a comprehensive overview of Nepal’s demographic dynamics as revealed by the census, highlighting population growth trends, gender distribution, household structures, ecological and provincial demographics, literacy progress, migration, and emerging social dimensions. The results reveal a population of 29,164,578 with an annual growth rate of 0.92 percent, an unprecedented decline in fertility to 1.85 (below replacement level), and accelerated urbanization with two-thirds of the population now living in urban areas, and the first recognition of third-gender individuals. The census findings are presented with statistical tables, charts, and critical analysis, establishing a vital reference point for policymakers, academics, and development practitioners. These demographic shifts are interpreted within Nepal’s socio-economic and historical context, underscoring their implications for governance, planning, and sustainable development.